0
$\begingroup$

I am given three summations as follows:

$S_0 = \sum_{k=0}^n x^k$

$S_1 = \sum_{k=1}^n kx^k$

$S_2 = \sum_{k=1}^n k^2x^k$

The question is how do I express $S_2$ in terms of $S_1$ and $S_0$?

it is given that n is in natural numbers, x is real, and x is not equal to 1.

I am struggling to understand how to approach this problem. The first step that I took is reindexing so that they all begin with k=0, since that term would be 0 for $S_1$ and $S_2$. Also I realize that these are all related by increasing the exponent of k. Unfortunately, I am unsure what to do with this information. Any hints on where to start would be appreciated!

$\endgroup$
  • $\begingroup$ I think the problem is about how to write $S_1$ and $S_2$ in terms of $S_0$. If this is the case try manipulations with derivatives. The derivative of a summation increase in 1 the starting position in the index. $\endgroup$ – Masacroso Nov 30 '15 at 0:58
  • $\begingroup$ My mistake. The question is how to write $S_2$ in terms of $S_1$ and $S_0$ $\endgroup$ – Taylor Nov 30 '15 at 1:47
  • $\begingroup$ It is the same, use derivatives. Write $S_0$ in terms without the summation symbol and derive it ($\frac{\rm d}{\rm dx}S_0$) and see what happen. $\endgroup$ – Masacroso Nov 30 '15 at 3:03
0
$\begingroup$

You can write $S_0$ as $\frac{1-x^{n+1}}{1-x}$ (are you OK with that?) and then rewrite $S_1$ as

$S_1 = \sum_{k=1}^{n} k x^k = \frac{1}{x} \sum_{k=1}^{n} k x^{k-1}$. You can then use $\sum_{k=1}^{n} k x^{k-1} = \frac{d S_0}{d x}$.

For $S_2$ use $\frac{d S_1}{d x} = \sum_{k=1}^{n} k^2 x^{k-1} = \frac{1}{x} S_2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.